2015
DOI: 10.1016/j.rser.2015.04.087
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of solar collectors—A review

Abstract: Given rapid depletion of conventional energy sources and environmental degradation caused by their over exploitation, the renewable energy sources are believed to be the future. Technologies utilizing renewable energy sources differ significantly from one another, not only with regard to technical and economic aspects but also in relation to their reliability, maturity, and operational experience in utility scale conditions. Technologies used to harness solar energy have emerged as the most promising and matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
88
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(93 citation statements)
references
References 108 publications
0
88
0
5
Order By: Relevance
“…The single-axis tracking collectors are orientated on a North-South axis and tracked on an East-West axis. The second category has two tracking axes that move perpendicularly to each other (Suman, Khan, & Pathak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The single-axis tracking collectors are orientated on a North-South axis and tracked on an East-West axis. The second category has two tracking axes that move perpendicularly to each other (Suman, Khan, & Pathak, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Authors suggested future research workto minimize uncertainties in nanofluids by doing study in 2phase manner.Sharafeldinet al [8]did study on flat plate solar collector for finding the performance by using WO 3 /Water nanofluid. Suman et al [9]has reviewed comprehensively methodologies used to examined the collector performance. He reported that improvement in various solar collectors can be enhanced by applying collector coating, geometrical modifications and stability of nanoparticles in ethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 40% of energy consumption and 36% of CO 2 emissions in the EU are caused by buildings, according to United Nations Environment Programme (UNEP). As a result, an increasing interest has been concentrated on the design of modern sustainable AC systems powered by renewables, especially the solar energy that is a universally inexhaustible natural and clean resource [1]. Hence, it can offer a reduction of the consumption, the demand, and the costs of energy, without decreasing the desired comfort.…”
Section: Introductionmentioning
confidence: 99%